SISTEMATIC LITERATURE REVIEW : EKSPLORASI ETNOMATEMATIKA PADA KERAJINAN TENUN - Rencitia; Aan Putra (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
The need to refer to culture to make it easier for students to plant mathematical concepts in understanding mathematics learning materials. One of them is weaving. This study aims to determine and analyze the Etnomathematical Exploration in weaving and its relation to mathematical concepts. The research method used is the Systematic Literatur Riview (SLR) mhetod. Data collection was carried out by reviewing all articles related to ethnomathematics in weaving that were published in the 2016-2021 period. The articles used in this study were 7 accredited national journal articles obtained from the Google Schoolar database. The results show that there are many weaving carfts that can be applied in learning mathematics, aspecially in Geometry.